EGFR mutations are associated with response to depatux-m in combination with temozolomide and result in a receptor that is hypersensitive to ligand. Issue 1 (9th December 2019) - Hoogstrate, Youri; Vallentgoed, Wies; Kros, Johan M; de Heer, Iris; de Wit, Maurice; Eoli, Marica; Sepulveda, Juan Manuel; Walenkamp, Annemiek M E; Frenel, Jean-Sebastien; Franceschi, Enrico; Clement, Paul M; Weller, Micheal; et al.
Abstract: Background: The randomized phase II INTELLANCE-2/EORTC_1410 trial on EGFR-amplified recurrent glioblastomas showed a trend towards improved overall survival when patients were treated with depatux-m plus temozolomide compared with the control arm of alkylating chemotherapy only. We here performed translational research on material derived from this clinical trial to identify patients that benefit from this treatment. Methods: Targeted DNA-sequencing and whole transcriptome analysis was performed on clinical trial samples. High-throughput, high-content imaging analysis was done to understand the molecular mechanism underlying the survival benefit. Results: We first define the tumor genomic landscape in this well-annotated patient population. We find that tumors harboring EGFR single-nucleotide variations (SNVs) have improved outcome in the depatux-m + TMZ combination arm. Such SNVs are common to the extracellular domain of the receptor and functionally result in a receptor that is hypersensitive to low-affinity EGFR ligands. These hypersensitizing SNVs and the ligand-independent EGFRvIII variant are inversely correlated, indicating two distinct modes of evolution to increase EGFR signaling in glioblastomas. Ligand hypersensitivity can explain the therapeutic efficacy of depatux-m as increased ligand-induced activation will result in increased exposure of the epitope to the antibody–drug conjugate. We also identified tumors harboring mutations sensitive to "classical" EGFR tyrosine-kinase inhibitors, providing a potential alternative treatment strategy. Conclusions: These data can help guide treatment for recurrent glioblastoma patients and increase our understanding into the molecular mechanisms underlying EGFR signaling in these tumors.